Long‐acting injectable antipsychotics for prevention and management of violent behaviour in psychotic patients. Issue 9 (4th September 2017) - Mohr, Pavel; Knytl, Pavel; Voráčková, Veronika; Bravermanová, Anna; Melicher, Tomáš
Summary: Background and Aims: It has been well established that long‐term antipsychotic treatment prevents relapse, lowers number of rehospitalisations, and also effectively reduces violent behaviour. Although violent behaviour is not a typical manifestation of schizophrenia or other psychotic disorders, the diagnosis of psychosis increases the overall risk of violence. One of the few modifiable factors of violence risk is adherence with medication. In contrast, non‐adherence with drug treatment and subsequent relapse increases risk of violent acts. Non‐adherence can be addressed partially by long‐acting injectable antipsychotics (LAI). The aim of our review was to examine the role of antipsychotic drugs, especially LAI, in prevention and management of violent behaviour in psychosis. Methods: This is a non‐systematic, narrative review of the data from open, naturalistic, retrospective, and population studies, case series, and post hoc analyses of randomised controlled trials. Search of electronic databases (PubMed, Embase) was performed to identify relevant papers. Results: Nine published papers (3 cross‐sectional chart reviews, 4 retrospective studies, 2 prospective, randomised trials) were found. The results indicated positive clinical and antiaggressive effects of LAI in psychotic patients with high risk of violent behaviour. Discussion: Reviewed evidence suggests that secured drug treatment with LAI may have clinical benefit in schizophrenia patients with high risk of violent behaviour. LAI significantly reduced the severity of hostility, aggressivity, number of violent incidents, and criminal offences. These findings are supported further by the empirical evidence from clinical practice, high rates of prescribed LAI to schizophrenia patients in high‐security and forensic psychiatric facilities. Conclusions: Available data encourage the use of LAI in forensic psychiatry, especially during court‐ordered commitment treatment.